(untitled) (Eurasian Journal of Philology Science and Education, 2015)
For an article "Linguosemiotic analysis of the translation of the tragedy by William Shakespeare" Othello "(based on the translation of A. Osmonov)" senior teacher of the methods of teaching English department Orozbaeva Gulbarchin Abdimazhitovna. The actuality of this research paper is due to the prospect for a comparative study linguosemiotic analysis of the tragedy William Shakespeare’s Othello and its translation to the Kyrgyz language. In addition to being work on comparative analysis of the originals and their translations, and the semiotic works given insufficient attention. Semiotic study is timely and presents both theoretical and practical interest that defines the goals and objectives of this analysis. The results obtained in the article have scientific value, since in this paper provides the base of semiotic studies of the Kyrgyz and English languages attracted attention of researchers. in sufficient detail the author studied the words, phrases and stylistic paths conveying the main ideas of the tragedy, expressed in metametasemiotic level of analysis. The author in his work gives a detailed analysis of the text on metametasemiotic level. There is considered in detail the cultural concepts that convey the main ideas of the tragedy, expressed in semiotic, metasemiotic levels of analysis. Reviewed work is distinguished by a number of ideas and evidence. Scientific superwisor: doctor of philology, dozent Z. K Karaeva